COMPOSITION FOR DYEING KERATIN FIBERS - TSUZUKI SAKI; OZAWA RIMIKO (2017)
PROBLEM TO BE SOLVED: To provide a composition for dyeing keratin fibers using direct dye, the composition capable of preventing or reducing skin contamination with the direct dye on the skin, such as the scalp, while imparting a good cosmetic effect, for example good (or at least acceptable) coloring properties to the keratin fibers.SOLUTION: According to the preset invention, there is provided a composition in the form of a dye, preferably an O/W emulsion, for dyeing keratin fibers, preferably the hair. The composition comprises: (a) at least one direct dye; (b) at least one fatty substance; (c) at least one surfactant; (d) at least one monohydric alcohol other than the fatty substance of (b); (e) at least one specific diester compound; and (f) water. The composition according to the invention can prevent or reduce skin contamination with the direct dye on the skin, such as the scalp, while imparting a good cosmetic effect, for example good coloring properties to the keratin fibers.SELECTED DRAWING: None 【課題】直接染料を使用するが、頭皮等の皮膚への直接染料による皮膚汚染を防止又は低減することができ、一方で、優れた美容効果、例えば良好な(又は少なくとも許容可能な)着色特性をケラチン繊維に付与する、ケラチン繊維を染色するための組成物を提供すること。【解決手段】本発明は、ケラチン繊維、好ましくは毛髪を染色するための、好ましくはO/Wエマルションの形態の組成物であって、(a)少なくとも1種の直接染料と、(b)少なくとも1種の脂肪物質と、(c)少なくとも1種の界面活性剤と、(d)少なくとも1種の、(b)脂肪物質以外の一価アルコールと、(e)少なくとも1種の特定のジエステル化合物と、(f)水とを含む、組成物に関する。本発明による組成物は、頭皮等の皮膚への直接染料による皮膚汚染を防止又は低減することができ、一方で、良好な美容効果、例えば良好な着色特性をケラチン繊維に付与する。【選択図】なし